Rediscovery of the critically endangered ‘scarce yellow sally stonefly’ Isogenus nubecula in United Kingdom after a 22 year period of absence - Davy-Bowker, John; Hammett, Michael J.; Mauvisseau, Quentin; Sweet, Michael J. (Zootaxa, 2018)
The critically endangered ‘scarce yellow sally stonefly’ Isogenus nubecula (Newman, 1833) (Plecoptera: Perlodidae) was rediscovered in the United Kingdom (UK) in 2017. This rediscovery comes after a 22-year period of absence despite numerous surveys since its last record in 1995. This species is one of the rarest stoneflies in the UK and Europe and its rediscovery is of international significance, being the westernmost point in Europe where the species is found, with the next nearest populations occurring in Austria and western Hungary, Slovakia, and central Sweden. The species is classed as pRDB2 (vulnerable), however is not listed in the British Red Data Book despite only being present (as far as records detail) in one river, the River Dee in North Wales, UK. Only fourteen individuals were caught and the need for conservation of this rare stonefly is therefore of paramount importance. We have made recommendations for the need to increase survey effort using environmental DNA (eDNA) techniques in order to fully understand the species range in this river and those in the surrounding area. The DNA sequence of I. nubecula has been uploaded on GenBank for further genetic studies. Captive rearing could also be explored with possible reintroductions to sites within its former UK range.